Effects of Occupational Safety and Motivation on Employee Performance: A Study on Fire Department of Karawang - Arafat, Zarisnof; Isyanto, Puji; Rahmayanti, Rima (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to determine the effect of occupational safety and motivation to employee performance on the Fire Department Karawang. As we know the speed factor in tackling the fire is needed because it involves the safety of human lives and valuable assets. Therefore in addition to completeness of equipment and technical skills required in the field of safety and the motivation of the employees of the fire department is very high. The success of managing fire quickly and minimize workplace accidents will cause a sense of job satisfaction of employees karawang firefighters.